Mathematical Models of Brain Dynamics: Progress and Perspectives - Borisenok, Sergey (Amer Inst Physics, 2 Huntington Quadrangle, Ste 1No1, Melville, Ny 11747-4501 Usa, 2012)
We describe micro-, meso- and macroscopic levels for mathematical models of brain dynamics (spike neural model, K-models, quantum brain dynamics) and discuss some perspectives of their development.
Keywords: brain dynamics; neural clusters; hierarchy approach; beyin dinamikleri; sinirsel kümeler; hiyerarşi yaklaşımı